Retransmission scheme for contention‐based data transmission systems. Issue 2 (15th January 2018) - Li, Lin; Long, Hang; Zhao, Long; Yang, Haojun; Zheng, Kan
Abstract : In conventional schedule‐based wireless transmission system, frequent interactions between devices and access networks lead to significant signalling overhead, and thus limit the development of low‐latency applications. Contention‐based data transmission (CBDT) is widely used as a promising solution to address the above issues. In this study, the authors propose a detection‐based retransmission scheme for CBDT to further reduce the delay‐outage probability which cannot be avoided due to collision. In this scheme, each device simultaneously monitors the occupied resource blocks during data transmission. When a collision event is detected, the retransmission for this packet is determined without waiting for the acknowledgment message from the receiver. The reliability performance is significantly improved for low‐latency applications, since the possible retransmission times for each packet is increased within the limited transmission period. In addition, the impacts of imperfect detection on extra transmission load and packet loss are analysed in detail. The simulation and analytical results demonstrate that the detection‐based scheme significantly improves the reliability of CBDT.